PENERAPAN METODE ADDIE PADA PENGEMBANGAN KOMIK INTERAKTIF SEBAGAI MEDIA EDUKASI KEAMANAN DATA PRIBADI BAGI ANAK - Dimas Sasongko; Septiyati Purwandari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
In 2020 there was an increase in internet users from the elementary school level, reaching 35.97%. Children's activity in cyberspace has negative impacts, such as the personal data they have can be spread, and there is a great potential for violations of children's rights. They become targets or victims of cybercrime. According to UNICEF data, in 2017, there were five million child profiles and accounts that hackers in the digital world stole. More and more children are using the Internet, but education regarding personal data security with media that suits children's needs is still limited. Therefore, this research will design, design, and build Android-based interactive comics that will be used as educational media for children about personal data security. This research aims to familiarize oneself with personal data security and protection strategies. The specific objective of this study is to make comics by compiling storyline scenarios according to everyday life practices. This research uses the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). This research produces a collection of comic strips about personal data security packaged in an Android-based application. Based on the test, the perspective of test participants regarding interactive comic applications is that they have acceptability ranges in the acceptable category, have a grade scale with category C, and have an adjective rating with the good category.